The Deep Ocean's Carbon Exhaust. Issue 7 (21st July 2022) - Chen, Haidi; Haumann, F. Alexander; Talley, Lynne D.; Johnson, Kenneth S.; Sarmiento, Jorge L.
Abstract: The deep ocean releases large amounts of old, pre‐industrial carbon dioxide (CO2 ) to the atmosphere through upwelling in the Southern Ocean, which counters the marine carbon uptake occurring elsewhere. This Southern Ocean CO2 release is relevant to the global climate because its changes could alter atmospheric CO2 levels on long time scales, and also affects the present‐day potential of the Southern Ocean to take up anthropogenic CO2 . Here, year‐round profiling float measurements show that this CO2 release arises from a zonal band of upwelling waters between the Subantarctic Front and wintertime sea‐ice edge. This band of high CO2 subsurface water coincides with the outcropping of the 27.8 kg m −3 isoneutral density surface that characterizes Indo‐Pacific Deep Water (IPDW). It has a potential partial pressure of CO2 exceeding current atmospheric CO2 levels (∆PCO2 ) by 175 ± 32 μatm. Ship‐based measurements reveal that IPDW exhibits a distinct ∆PCO2 maximum in the ocean, which is set by remineralization of organic carbon and originates from the northern Pacific and Indian Ocean basins. Below this IPDW layer, the carbon content increases downwards, whereas ∆PCO2 decreases. Most of this vertical ∆PCO2 decline results from decreasing temperatures and increasing alkalinity due to an increased fraction of calcium carbonate dissolution. These two factors limit the CO2 outgassing from the high‐carbon content deep waters on more southerly surface outcrops. Our results imply that the response of Southern Ocean CO2 fluxes to possible future changes in upwelling are sensitive to the subsurface carbon chemistry set by the vertical remineralization and dissolution profiles. Key Points: Deep ocean CO2 release arises from high potential CO2 partial pressure in subsurface water between the Subantarctic Front and sea‐ice edge Maximum subsurface potential CO2 is connected to the outcrop of upwelling Indo‐Pacific Deep Water (IPDW), rich in remineralized organic carbon High alkalinity and low temperature limit CO2 release from higher carbon‐content deep water outcropping south of IPDW